Обеспечение эффективности поддержки малого бизнеса в посткризисный период (Путеводитель предпринимателя, 2020)
The article reviews the issues of creation and development of the entrepreneurial subject segment. The segment in question is the basis for social restructuring that ensures the preparation of the country’s population as well as the transition of the entire economy to anti-crisis management methods.